Developing SMART Goals for Your Organization: FE577/FE577, 11/2005 - Cothran, Henry M.; Wysocki, Allen F. (EDIS, 2005)
Individuals may set goals to achieve a personal objective such as career advancement. This publication is designed to introduce a sequential process for setting goals. It begins by defining a goal and identifying reasons for setting goals. It then describes a process based on the acronym SMART for developing and implementing goals. This document is FE577, one of a series of the Food and Resource Economics Department, UF/IFAS Extension. Original publication date November 2005. FE577/FE577: Developing SMART Goals for Your Organization (ufl.edu)